2009
DOI: 10.1104/pp.109.147116
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Possible Roles for B Class MADS Box Genes in Regulation of Perianth Formation in Orchid

Abstract: To investigate sepal/petal/lip formation in Oncidium Gower Ramsey, three paleoAPETALA3 genes, O. Gower Ramsey MADS box gene5 (OMADS5; clade 1), OMADS3 (clade 2), and OMADS9 (clade 3), and one PISTILLATA gene, OMADS8, were characterized. The OMADS8 and OMADS3 mRNAs were expressed in all four floral organs as well as in vegetative leaves. The OMADS9 mRNA was only strongly detected in petals and lips. The mRNA for OMADS5 was only strongly detected in sepals and petals and was significantly down-regulated in lip-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 91 publications
6
97
1
Order By: Relevance
“…However, our quantitative analysis demonstrates that in the labellum of all species analyzed the mRNA levels of both clade-1 and -2 DEF-like genes are up to ten times lower than in the other perianth organs (Figure 2). These results are comparable, and in general agreement, with the expression of OMADS5 (clade 1) and OMADS3 (clade 2) in the organs of wild-type and peloric flowers of Oncidium Gower-Ramsey (Epidendroideae) (Chang et al, 2010). However, these authors argue that OMADS5 (clade 1) is absent from the labellum, and has a reduced level of expression in the ectopic labellum-like organs of the mutants analyzed.…”
Section: 00e+01supporting
confidence: 69%
See 4 more Smart Citations
“…However, our quantitative analysis demonstrates that in the labellum of all species analyzed the mRNA levels of both clade-1 and -2 DEF-like genes are up to ten times lower than in the other perianth organs (Figure 2). These results are comparable, and in general agreement, with the expression of OMADS5 (clade 1) and OMADS3 (clade 2) in the organs of wild-type and peloric flowers of Oncidium Gower-Ramsey (Epidendroideae) (Chang et al, 2010). However, these authors argue that OMADS5 (clade 1) is absent from the labellum, and has a reduced level of expression in the ectopic labellum-like organs of the mutants analyzed.…”
Section: 00e+01supporting
confidence: 69%
“…This suggests that the observed reduction in the expression of clade-1 genes in the inner lateral tepals is not required for the establishment of labellum-like organ identity. Although both our analysis and that of Chang et al (2010) detected expression of clade-2 genes in peloric flowers of Phalaenopsis hybrid 'Athens' or Oncidium Gower Ramsey, respectively, an earlier expression analysis employing northern-blot hybridization reported that expression of the clade-2 gene ortholog, PeMADS5, of Phalaenopsis equestris is absent from the perianth and gynostemium of a similar three-labellum mutant (Tsai et al, 2004). As both qRT-PCR and northern-blot hybridization are highly sensitive techniques, a feasible explanation for these contrasting results is that the mutants analyzed have similar phenotypes but a different genetic or epigenetic basis, as has already been suggested for other cases of orchid pelorism (Rudall and Bateman, 2003).…”
Section: 00e+01mentioning
confidence: 94%
See 3 more Smart Citations